Sarcoidosis, a report from Guilan (an Iranian Northen province) (2001-09) - Alavi, Ali; Akhoundzadeh, Niloofar; Fallah Karkan, Morteza (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Sarcoidosis is a chronic multiorgan autoimmune disorder that affects all racial and ethnic groups and occurs at all ages.Objective:The aim of this study was to assess the clinical and epidemiological features of sarcoidosis patients in a referral clinic of pulmonary disease in city of Rasht (Guilan-Iran).Method: This retrospective study was done by reviewing sarcoidosis patient's records containing demographic, sign and symptom and clinical data in a pulmonary clinic in Rasht from 2001-09. All statistical analyses were achieved using SPSS.Results: most common signs and symptoms were respiratory, systemic and musculoskeletal complaints. According to Chest X-Ray, 61.3% had bilateral hilar lymphadenopathy (BHL) alone (stage 1), and 24.2% had BHL plus parenchymal involvment (stage 2). The most common abnormal finding in spirometry was small airway disease (20.3%).The follow-up data showed that 178 patients (45.2%) had significant improvement clinically, radiologically or both.Conclusion:It seems many clinical and radiological aspects of sarcoidosis in our patients are similar to other series. However, presentation with Lofgren’s syndrome is a common feature and skin (n=48, 12.3%) and eye (n=19, 4.8%) involvement are less frequent. There is significant difference between west and east of Guilan in relation to referred patients (12.9 % vs 78.5% respectively).Of course this may be due to referral issues of patients and medical teamwork connections